Racism in the 1980's : a response. - Victorian Ethnic Affairs Commission. Division of Research and Policy (East Melbourne : Office of the Minister for Ethnic Affairs, 1984)
Non-Aboriginal material; concerned with attitudes towards immigration.
Cover title.
At head of title: Ministerial discussion paper.
"This paper is the result of the work done by the Research and Policy Division of the Ethnic Affairs Commission."--Pref.
Bibliography: leaves 39-40.
Keywords: Racism -- Australia; Race relations - Non-Indigenous.; Settlement and contacts - Ethnic groups, immigration and multiculturalism; Australia -- Ethnic relations; Australia -- Emigration and immigration; Victoria (Vic)